1989
DOI: 10.1093/ajh/2.7.563
|View full text |Cite
|
Sign up to set email alerts
|

Na,K-ATPase Activity in Renal Tubule Cells From Milan Hypertensive Rats

Abstract: Several abnormalities of cation transport have been described in the Milan hypertensive rats (MHS). In this study we examined Na,K-ATPase activity in proximal convoluted tubules (PCT) cells and medullary thick ascending limb of Henle cells (TAL) from MHS and from the Milan normotensive rats (MNS). Na,K-ATPase activity was determined as 32P-ATP hydrolysis in single tubule segments. Na,K-ATPase activity (pmol Pi/mm t/h) was significantly higher in MHS than MNS both in PCT (903 +/- 227 n = 8 v 506 +/- 285 n = 12)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…15 Na ϩ /K ϩ -ATPase activity was also found enhanced in the medullary tissue of Milan hypertensive rats. 17 Similarly, glucose increases O 2 consumption and Na ϩ /H ϩ -exchanger activity in proximal tubules of diabetic rat models 16 and stimulates the baseline activity of the Na ϩ /K ϩ -ATPase pump in renal tubules, including mTAL. 18 It is believed to be the major substrate driving oxygen consumption and production of ATP and Na ϩ /K ϩ -ATPase related activity in mTAL.…”
Section: ·؊ Productionmentioning
confidence: 98%
“…15 Na ϩ /K ϩ -ATPase activity was also found enhanced in the medullary tissue of Milan hypertensive rats. 17 Similarly, glucose increases O 2 consumption and Na ϩ /H ϩ -exchanger activity in proximal tubules of diabetic rat models 16 and stimulates the baseline activity of the Na ϩ /K ϩ -ATPase pump in renal tubules, including mTAL. 18 It is believed to be the major substrate driving oxygen consumption and production of ATP and Na ϩ /K ϩ -ATPase related activity in mTAL.…”
Section: ·؊ Productionmentioning
confidence: 98%
“…Which is the true GFR in MHS and MNS? When the two results were incorporated within the framework of the other results obtained by studying the cellular response to osmotic pressure (59) and the tubular function measured in isolated kidneys (121,122) in isolated tubular cells (101) or in cell membranes prepared from these kidneys (52,72), it is clear that the GFR is elevated in MHS.…”
Section: Personal Approachmentioning
confidence: 99%
“…A large deal of these experiments were carried out in a strain of genetically hypertensive rats (MHS, Milan hypertensive strain) 1 that we developed along with their normotensive controls (MNS, Milan normotensive strain) (1). These studies, based on experimental procedures like MHS/MNS kidney cross-transplantation (2, 3), renal function measurements performed both in isolated kidneys (4,5) and in intact animals (6,7) as well as in whole cells (8,9) and cell membranes (10,11), indicated that the primary defect leading to MHS hypertension was a faster ion transport rate across tubular cells (1). As the same transmembrane ion transport differences between MHS and MNS were also found in erythrocytes (1), these cells were used to demonstrate that the MHS abnormalities were genetically determined within the stem cells and genetically associated to hypertension (12).…”
Section: Introductionmentioning
confidence: 99%